Sosialisasi Sertifikasi Halal dan Manajemen Keuangan Untuk Meningkatkan Daya Saing UMKM - Amelia, Amelia; Nadiya, Nadiya; Khaira, Fathul; Darussalam, Rizky Kinenara (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The involvement of micro, small, and medium enterprises (MSMEs) plays a central role in promoting economic growth in Indonesia, including Aceh Province. To enhance their competitiveness, comprehensive support from various stakeholders is essential, with a focus on knowledge improvement, fostering independence, and expanding access to resources. Strategic initiatives to strengthen MSMEs are through halal product certification and improving the financial management of business owners. Facilitated by the Community Service Team, this activity has proven effective in raising awareness among MSME’s owners about the importance of halal certification to boost product competitiveness in the market. Additionally, the activity provides practical skills in basic financial record-keeping, which is essential for more professional business management